Improving ancestry distinctions among Southwest Asian populations. (July 2018) - Bulbul, Ozlem; Speed, William C.; Gurkan, Cemal; Soundararajan, Usha; Rajeevan, Haseena; Pakstis, Andrew J.; Kidd, Kenneth K.
Highlights: Previous studies identified Europe and Southwest Asia as a "Continental Region". 2568 samples of 39 populations from this region plus East Africa were studied. 264 Ancestry Informative SNPs (AISNPs) were typed on new 299 individuals. The two-tier approach was applied for finer scale ancestry assignment. 86 AISNPs define refined ancestry among European and Southwest Asian populations, as a second-tier panel. Abstract: The Kidd Lab panel of 55 AISNPs can provide up to 10 statistically relevant biogeographic groupings of a global set of populations. A second-tier panel would be useful for increasing the accuracy for further differentiation of populations within a specific global grouping. Because recent advances in massively parallel sequencing (MPS) methods allow the genotyping of many more SNPs, we are now identifying additional SNPs to provide refined discrimination among regional subsets of populations; Southwest Asia and the nearby Mediterranean region (SWA) is our current target for such a "second tier" panel. We selected the potentially best SNPs from various sources: our own laboratory database (>4600 SNPs), AISNP panels (Kidd 55 and Seldin 128 SNP panels), and published papers reporting European and SW Asian populations. Rosenberg's Informativeness, Fst, and allele frequency heatmap matrices are used to determine the best SNPs for the region. A total of 2568 individuals, from 39 different populations ranging from North-East Africa through the SW Asia and Europe to the Ural Mountains, were included in the refinement processes and analyses. Heatmap, PCA, Structure (K = 4), and ancestry inference for selected individuals with an in-lab version of FROG-kb analyses indicate that these 86 AISNPs provide the basis for building an improved, optimized panel of AISNPs that collectively provide additional information on differences among populations in that part of the world. Testing this panel with additional populations from the area and with new SNPs and/or microhaplotypes is expected to improve the panel.